One fold of rectangle can know everything?

Geometry Level 3

A rectangular paper has integer side lengths. Now the paper is folded so that a pair of diagonally opposite vertices coincide. The length of the resulting crease is 65.

Find the perimeter of the paper.


The answer is 408.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

David Vreken
Jul 16, 2018

Let Q Q , R R , S S , and T T be the vertices of the rectangle, M N MN be the paper's crease with length 65 65 , P P be the intersection of the crease and the paper's diagonal, and M O MO be perpendicular to S T ST , as shown below. Also let a a and b b be the lengths of the paper's two sides Q T QT and S T ST respectively, and c c be the length of N T NT .

Since Q Q reflects on S S in crease M N MN through P P , Q P P S QP \cong PS and S P N Q P N \angle SPN \cong \angle QPN . Since P N P N PN \cong PN by the reflexive property, S P N Q P N \triangle SPN \cong \triangle QPN by SAS congruence. Therefore, N Q = N S = b c NQ = NS = b - c , and by Pythagorean's Theorem on N T Q \triangle NTQ , a 2 + c 2 = ( b c ) 2 a^2 + c^2 = (b - c)^2 . Solving this equation for c c gives c = b 2 a 2 2 b c = \frac{b^2 - a^2}{2b} .

By rotational symmetry, R M = N T RM = NT , and since R M S O RMSO is a rectangle, S O = R M SO = RM . Therefore, R M = S O = N T = c RM = SO = NT = c . Since b = S O + O N + N T b = SO + ON + NT , b = O N + 2 c b = ON + 2c , and so O N = b 2 c ON = b - 2c . Since Q M O T QMOT is a rectangle, M O = Q T = a MO = QT = a . Therefore, by Pythagorean's Theorem on M O N \triangle MON , a 2 + ( b 2 c ) 2 = 6 5 2 a^2 + (b - 2c)^2 = 65^2 .

Substituting c = b 2 a 2 2 b c = \frac{b^2 - a^2}{2b} into a 2 + ( b 2 c ) 2 = 6 5 2 a^2 + (b - 2c)^2 = 65^2 gives a 2 + a 4 b 2 = 4225 a^2 + \frac{a^4}{b^2} = 4225 , and solving this equation for b b gives b = a 2 4225 a 2 b = \frac{a^2}{\sqrt{4225 - a^2}} .

If a a and b b are integers in the equation b = a 2 4225 a 2 b = \frac{a^2}{\sqrt{4225 - a^2}} for a > 0 a > 0 and b > 0 b > 0 , then s = 4225 a 2 s = \sqrt{4225 - a^2} must be an integer. The only possibilities for ( a , s ) (a, s) with integer solutions for a > 0 a > 0 are ( 16 , 63 ) (16, 63) , ( 25 , 60 ) (25, 60) , ( 33 , 56 ) (33, 56) , ( 39 , 52 ) (39, 52) , ( 52 , 39 ) (52, 39) , ( 56 , 33 ) (56, 33) , ( 60 , 25 ) (60, 25) , and ( 63 , 16 ) (63, 16) , and out of these possibilities the only resulting integer value for b = a 2 s b = \frac{a^2}{s} is ( 60 , 25 ) (60, 25) , which means a = 60 a = 60 and b = 6 0 2 25 = 144 b = \frac{60^2}{25} = 144 .

Therefore, the only possible side lengths of the rectangular paper are 60 60 and 144 144 , and its perimeter is P = 2 60 + 2 144 = 408 P = 2 \cdot 60 + 2 \cdot 144 = \boxed{408} .

How did you generate your list of (a,s)? One way would be to recognize pythagorean triples and to write 65 as k ( m 2 + n 2 ) k(m^2+n^2) . Is there a different/better way to do this?

John Ross - 2 years, 10 months ago

Log in to reply

I used the table function on the graphing calculator to check all integers 0 < a < 65. I couldn't think of a better way to do this.

David Vreken - 2 years, 10 months ago

Log in to reply

Ok, just curious if there was a better way to do it than my method ( (s,a,65) forms a pythagorean triple, so 65 = k ( m 2 + n 2 ) 1 ( 64 + 1 ) , 1 ( 49 + 16 ) , 5 ( 9 + 4 ) , 13 ( 4 + 1 ) 65=k(m^2+n^2) \implies 1(64+1), 1(49+16), 5(9+4), 13(4+1) )

John Ross - 2 years, 10 months ago

Log in to reply

@John Ross That's a better method than mine!

David Vreken - 2 years, 10 months ago

Remember 4225 4225 comes from 6 5 2 65^2 , and 65 = 5 × 13 65=5\times 13 , so 6 5 2 = 5 2 × 1 3 2 65^2=5^2\times 13^2

Also, 5 2 = 3 2 + 4 2 5^2=3^2+4^2 and 1 3 2 = 5 2 + 1 2 2 13^2=5^2+12^2

Let's first substitute 5 2 = 3 2 + 4 2 5^2=3^2+4^2 , we get 6 5 2 = ( 3 2 + 4 2 ) × 1 3 2 = ( 3 × 13 ) 2 + ( 4 × 13 ) 2 65^2=(3^2+4^2)\times 13^2=(3\times 13)^2+(4\times 13)^2

If we substitute 1 3 2 = 5 2 + 1 2 2 13^2=5^2+12^2 instead, we have 6 5 2 = ( 5 × 5 ) 2 + ( 5 × 12 ) 2 65^2=(5\times 5)^2+(5\times 12)^2

Now if we substitute both at the same time, we have 6 5 2 = ( 3 2 + 4 2 ) × ( 5 2 + 1 2 2 ) = ( 3 × 5 ) 2 + ( 3 × 12 ) 2 + ( 4 × 5 ) 2 + ( 4 × 12 ) 2 = [ ( 3 × 5 ) + ( 4 × 12 ) ] 2 2 ( 3 × 5 ) ( 4 × 12 ) + ( 4 × 5 ) 2 + ( 3 × 12 ) 2 = [ ( 3 × 5 ) + ( 4 × 12 ) ] 2 + [ ( 3 × 12 ) ( 4 × 5 ) ] 2 65^2=(3^2+4^2)\times (5^2+12^2)=(3\times 5)^2+(3\times 12)^2+(4\times 5)^2+(4\times 12)^2=[(3\times 5)+(4\times 12)]^2-2(3\times 5)(4\times 12)+(4\times 5)^2+(3\times 12)^2=[(3\times 5)+(4\times 12)]^2+[(3\times 12)-(4\times 5)]^2

In the same manner, 6 5 2 = ( 3 × 5 ) 2 + ( 3 × 12 ) 2 + ( 4 × 5 ) 2 + ( 4 × 12 ) 2 = [ ( 3 × 12 ) + ( 4 × 5 ) ] 2 2 ( 3 × 12 ) ( 4 × 5 ) + ( 3 × 5 ) 2 + ( 4 × 12 ) 2 = [ ( 3 × 12 ) + ( 4 × 5 ) ] 2 + [ ( 4 × 12 ) ( 3 × 5 ) ] 2 65^2=(3\times 5)^2+(3\times 12)^2+(4\times 5)^2+(4\times 12)^2=[(3\times 12)+(4\times 5)]^2-2(3\times 12)(4\times 5)+(3\times 5)^2+(4\times 12)^2=[(3\times 12)+(4\times 5)]^2+[(4\times 12)-(3\times 5)]^2

We now express 6 5 2 65^2 into 4 different sum of 2 squares, and there are your 8 possibility of a a 's

Raymond Chan - 2 years, 10 months ago

Log in to reply

@Raymond Chan Wow, this is great!

David Vreken - 2 years, 10 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...